2020
DOI: 10.1002/cpsc.121
|View full text |Cite
|
Sign up to set email alerts
|

From Hair to iPSCs—A Guide on How to Reprogram Keratinocytes and Why

Abstract: Keratinocytes, as a primary somatic cell source, offer exceptional advantages compared to fibroblasts, which are commonly used for reprogramming. Keratinocytes can beat fibroblasts in reprogramming efficiency and reprogramming time and, in addition, can be easily and non-invasively harvested from human hair roots. However, there is still much to know about acquiring keratinocytes and maintaining them in cell culture. In this article, we want to offer readers the profound knowledge that we have gained since our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Lentiviral reprogramming is a well-established technique to deliver the reprogramming factors to the host cell [ 22 ]. It has been shown that the lentiviral transfection of keratinocytes shows a very high reprogramming efficiency [ 13 ]. KGM2 is used for reprogramming since its media composition is comparable with the EpiLife medium.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lentiviral reprogramming is a well-established technique to deliver the reprogramming factors to the host cell [ 22 ]. It has been shown that the lentiviral transfection of keratinocytes shows a very high reprogramming efficiency [ 13 ]. KGM2 is used for reprogramming since its media composition is comparable with the EpiLife medium.…”
Section: Resultsmentioning
confidence: 99%
“…This method has been previously described in detail [ 13 ]. In short: HFs were obtained from seven different, healthy donors ( Table S1 in Supplementary Materials ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two articles provide novel information on technologies to reprogram cells to induced pluripotent stem cells (iPSC). The starting material in one of these articles, by Klingenstein and colleagues (Klingenstein, Klingenstein, Kleger, & Liebau, 2020), are keratinocytes from hair samples. These cells have the advantage of being easily accessible, and can even be acquired from different areas in the world without special transport requirements.…”
Section: Introductionmentioning
confidence: 99%